Mechanical and thermal properties versus effective cubic lattice constant in Cu2-II-IV-VI4 quaternary compounds - Djellal, Marouane; Mebarki, Aymen; Benmakhlouf, Abdelfateh; Daoud, Salah (International Journal of Advanced Chemistry, 2022)
The present work aims to study the dependence of the bulk modulus B and the Debye temperature Î¸D with the effective cubic lattice constant aeff of some Cu2-II-IV-VI4 compounds. We are also studied the correlation between the bulk modulus B, the Debye temperature Î¸D, the microhardness H and the melting point Tm.The fits of the data of the bulk modulus B and the Debye temperature Î¸D versus the effective cubic lattice constant aeff show that B of Cu2-II-IV-VI4 semiconducting materials decreases almost linearly with increase of the effective cubic lattice constant aeff, while that of Debye Temperature Î¸D decreases exponentially with a rising of the effective cubic lattice constant aeff. The coefficients of the correlation were found at around -0.78 for the bulk modulus B, and at around -0.94 for the Debye temperature, respectively.For the bulk modulus B, the best fit was obtained using the following expression: B = - 596.52 aeff + 393.4, where B is expressed in GPa, and aeff in nm, while that of Î¸D is: Î¸D = 165.46 + 3.8 exp (-57.2 aeff), respectively. The average error on the estimation of B was found at around 10%, while that on the estimation of Î¸D is only around 4.5%, respectively. Our expressions perhaps used with high accurate to predict the bulk modulus B and the Debye temperature Î¸D of other quaternary Cu2-II-IV-VI4 semiconducting materials.